Progress in the Mechanism of Autophagy and Traditional Chinese Medicine Herb Involved in Dementia - Tao, Pengyu; Ji, Jing; Gu, Simeng; Wang, Qian; Xu, Yuzhen (Frontiers in Pharmacology, 2022)
Dementias is a kind of neurodegenerative disease, which occur among the aging population. And current therapeutic outcome for dementia are limited. The medical use of herbal plant has a rich history in traditional Chinese medicine practice for thousands of years. Herbal medicine (HM) may provide a positive effect for prevention and treatment in dementia. As an alternative treatment to dementia, there has been a growing interest in HM extracts in scientific community as results of its promising study result, mainly in animal experiment. At the molecular level, HM extracts triggers autophagy and reduces generation of ROS while inhibit inflammation and reduce neurotoxicity. Experiments in both vivo and vitro have identified certain potential of HM extracts and natural products as an important regulator factor in mediating autophagy, which might contribute to the improvement of dementia. This brief review not only summarize the mechanism of autophagy in dementia, but also offer a general understanding of therapeutic mechanism of HM extracts in treating dementia as well as evaluated the potential clinical practice of HM in general.